Zoning of Groundwater Pollution Prone Areas as the Fundament of Water Supply Planning in Surakarta - Alif Noor Anna (Universitas Muhammadiyah Surakarta, 2004)
The researh is carried out at the basi pillar in Surakarta that is estimated has a clear different at ground water quality. The goals of the research area 1) to know actually the distribution of arial zoning at pollution level of the groundwater; 2) to determine the priority scale of clean water supply. Data analysis used in the researh are tendentious analysis and geographical information system. The result shows that groundwater quality at the research place decreases. It can be proved by tendentious analysis that most of the groundwater quality conentration parameter – after being examined – the lower plae, the higher conentration. There are 21 quality parameters used for that research, 15 out of those have an inclining tendency, while the others are flat and decline. The result of 2 overlapping maps, atual zoning and potential zoning, shows that there is mismatching of risky polluted area. It is caused by human fators, some of them are population density, well construction, bad sanitation, individual septi tank, and industrial disposal from irrigation. Based on the result of the research, clean water district corporation is expected to be able to determine priority scale of clean water supply to Surakarta and its surrounding.